MENINGKATKAN KEDISIPLINAN MASUK SEKOLAH MELALUI LAYANAN BIMBINGAN KELOMPOK TEKNIK SELF MANAGEMENT PADA SISWA TKJ SMK NU MA'ARIF KUDUS - Zulfa Nurul Ummah; Indah Lestari; Sucipto Sucipto (Jurnal Muria Research Guidance and Counseling (MRGC), 2022)
School entrance discipline is a whole measure of measures that ensure the necessary moral conditions, so that the educational process runs smoothly and is not interrupted. This study aims to obtain an increase in school entrance discipline and implementation of Group guidance services self management techniques in students TKJ SMK NU ma'arif Kudus. Data collection techniques used include interviews and observation techniques. The results proved that the results obtained scores, school entrance discipline score students get an increase of 48 from the initial score when the pre-cycle results obtained an average of 34 with very less category, cycle I obtained an average score of 46 with less category and in Cycle II obtained an average score of 70 with good category. This study should be applied teachers through Group guidance services self management techniques to be more optimal so that students can improve discipline in school well.